164k views
3 votes
Simplify the expression

3(6/5p + 4q + 6) - 2(9/5p + 8q + 3)
A. -4Q +12

B. 2/5p - 4Q +12

C. 28Q +12

D. 28Q +24

2 Answers

10 votes
A. -4q+12 sorry it’s it’s wrong
User Antun
by
5.2k points
10 votes

Answer:

We conclude that:


(18p)/(5)+12q+18-(18p)/(5)-16q-6=-4q+12

Hence, option A is true.

Explanation:

Given the expression


3\left((6)/(5)p+4q+6\right)-2\left((9)/(5)p+8q+3\right)

solving the expression


3\left((6)/(5)p\:+\:4q\:+\:6\right)\:-\:2\left((9)/(5)p\:+\:8q\:+\:3\right)=3\left((6p)/(5)+4q+6\right)-2\left((9p)/(5)+8q+3\right)

Expand
3\left((6p)/(5)+4q+6\right)=(18p)/(5)+12q+18


=(18p)/(5)+12q+18-2\left((9p)/(5)+8q+3\right)

Expand
-2\left((9p)/(5)+8q+3\right)=-(18p)/(5)-16q-6


=(18p)/(5)+12q+18-(18p)/(5)-16q-6

Group like terms:


=(18p)/(5)-(18p)/(5)+12q-16q+18-6

Add similar elements:
(18p)/(5)-(18p)/(5)=0


=12q-16q+18-6

Add similar elements: 12q-16q=-4q


=-4q+18-6


=-4q+12

Therefore, we conclude that:


(18p)/(5)+12q+18-(18p)/(5)-16q-6=-4q+12

Hence, option A is true.

User Tungken
by
5.0k points